A new Polynomial based Symmetric Key Algorithm using Polynomial Interpolation Methods - Hasija, Taniya; Ramkumar, K. R.; Singh, Bhupendra; Kaur, Amanpreet; Mittal, Sudesh Kumar (Proceedings (International Conference on Communication Systems and Network Technologies Online), 2023)
The main attributes of a security framework are Confidentiality, Authentication, and Data integrity. There are two main standards of cryptography algorithms categorized as private or symmetric and public or asymmetric algorithms, symmetric algorithms use one secret key to encrypt and decrypt payloads, the list includes Data Encryption Standard (DES), Advanced Encryption Standard (AES), RC5, Blowfish, and others, and asymmetric algorithms use key pairs consists of public and private keys, RSA, and Elliptic Curve Cryptography are two best examples of the same. In spite of their successful implementations, these standards suffer from various attacks, and the beginning of large-scale quantum is the biggest threat to the commonly used cryptography algorithms. In general, Public-key cryptography relies upon mathematical problems that are hard to be broken with the available computational power but it is believed that quantum computers can break them at polynomial solvable time in future. Quantum-safe cryptography refers to a new generation of algorithms that are resilient against attacks launched by both classical and quantum computers. This work designs and implements a novel cryptography standard using polynomial interpolations to make it both supercomputer and quantum safe.